Records of alien marine species in the shallow coastal waters of Chios Island (2009) - KATSANEVAKIS, S.; TSIAMIS, K. (Mediterranean Marine Science, 2009)
The shallow coastline of Chios Island was surveyed for the presence of any alien marine benthic species, during August 2009. Fourteen randomly selected sites were surveyed by snorkeling during standardized one-hour transects at depths between 0 and 10 m, and the presence of all identified alien benthic species was recorded. Six alien species were identified: Asparagopsis taxiformis, Caulerpa racemosa var. cylindracea, Stypopodium schimperi, Halophila stipulacea, Percnon gibbesi, and Siganus luridus. The green alga C. racemosa var. cylindracea was found in high densities in all the surveyed sites and was characterized as invasive in the island. The brown alga S. schimperi, the crab P. gibbesi, and the fish S. luridussustain established populations in the area. For three of the recorded marine alien species (S. schimperi, P. gibbesi, and S. luridus),Chios Island seems to be the northernmost margin of their geographical range in the Aegean Sea.